MODELS OF DESIGNING CREATIVE ACTIVITIES IN MOTHER TONGUE TEACHING - Aziza Khusenova (Galaxy International Interdisciplinary Research Journal, 2022)
In this article we are talking about how, in order to design the creative activity of students when teaching their native language, from the point of view of a teacher applying creative design, the following concepts are interrelated and subordinated: teacher and textbook, teacher and teaching materials, teacher and visual aids, student and textbook, student and teaching material, student and visual aids, from the point of view of the leading activity of the teacher engaged in designing during the lessons, the teacher and the project, the teacher and the student, the teacher and the student’s attachments, the student and the teaching materials. Project activity should be considered as part of the professional competence of a teacher, which represents the unity of theoretical and practical training for the implementation of pedagogical activity and characterizes professional quality.